2022
DOI: 10.1097/pai.0000000000001037
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage Repair Proteins, HSP27, and Phosphorylated-HSP90α as Predictive/Prognostic Biomarkers of Platinum-based Cancer Chemotherapy: An Exploratory Study

Abstract: Platinum analogs are commonly used for cancer treatment. There is increasing interest in finding biomarkers which could predict and overcome resistance, because to date there is no reliable predictive/prognostic marker for these compounds. Here we studied the immunohistochemical expression of proteins involved in DNA damage response and repair (γH2AX, 53BP1, ERCC1, MLH1, and MSH2) in primary tumor tissues from patients treated with platinum-based chemotherapy. Levels and localization of Heat Shock Protein (HSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Recently, we reported that nuclear p-Hsp90α in tumor tissues correlated with good clinical response in patients treated with platinum-based chemotherapy. 17 However, the clinical implications of p-Hsp90α in PBL from cancer patients remain still unknown. For the first time, we evaluated by immunocytochemistry the nuclear and cytoplasmic expression of p-Hsp90α in pre-chemotherapy PBL from cancer patients at basal conditions and after cPt exposure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, we reported that nuclear p-Hsp90α in tumor tissues correlated with good clinical response in patients treated with platinum-based chemotherapy. 17 However, the clinical implications of p-Hsp90α in PBL from cancer patients remain still unknown. For the first time, we evaluated by immunocytochemistry the nuclear and cytoplasmic expression of p-Hsp90α in pre-chemotherapy PBL from cancer patients at basal conditions and after cPt exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor tissues known to express γH2AX, 53BP1, and p-Hsp90α Thr 5/7 were included as positive controls as described previously. 17…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are also many studies on the development of markers to predict chemotherapy response based on these mechanisms, and these markers include the homologous recombination deficiency (HRD) score, 19 heat shock protein 90α (HSP90α), 20 and Kirsten rat sarcoma virus (KRAS) gene. 21 However, the most widely used biomarker in clinical practice is MSI status.…”
Section: Introductionmentioning
confidence: 99%